Design wizards and visual programming environments for GenVoca generators - Batory, D.; Gang Chen; Robertson, E.; Tao Wang (IEEE transactions on software engineering, 2000)
Domain-specific generators will increasingly rely on graphical languages for declarative specifications of target applications. Such languages will provide front-ends to generators and related tools to produce customized code on demand. Critical to the success of this approach will be domain-specific design wizards, tools that guide users in their selection of components for constructing particular applications. The authors present the P3 ContainerStore graphical language, its generator, and design wizard.